Pengaruh Menyikat Gigi dengan Siwak (Salvadora Persica) Terhadap pH Saliva - Yossy Juliarni; Gunawan Gunawan (Andalas Dental Journal, 2016)
Background: Salivary pH is one of factor which involved in caries development. Decreasing of salivary pH will cause enamel demineralization. Miswak (Salvadora persica) as a toothbrush because it has mechanical and chemical effects such as essential oil and bicarbonate which can stimulate salivary secretion. Thus, it will increase the buffer capacity and salivary pH lead to enamel remineralization. Objective: This study aimed to know the effect of toothbrushing with miswak (Salvadora persica) on salivary pH. Methods: The clinical experiment study with pre-test and post-test control group design. The sample of this study is the students of Faculty of Dentistry, Andalas University, Padang. There are 34 students that divided into two groups randomly that is case and control group. Case group used miswak while control group used conventional toothbrush, respectively brushing horizontally for 2 minutes. Salivary pH was measured using digital pH meter in scale of 0.0 to 14.0 with 0.1 sensitivity from pen type pH meter. The data analyzed by Shapiro-Wilk test continued by paired t-test and Mann-Whitney test. Results: paired t-test produced significant value p=0,001 in case group and p=0,000 in control group. Mann-Whitney test produced significant value p=0.317. There was no significant difference in statistic among these groups. Conclusion: Toothbrushing with miswak has effect on salivary pH. Miswak as effective as toothbrush on salivary pH. Keywords:Toothbrushing, miswak (Salvadora persica), Salivar